Changing Attitudes toward Material Wealth in Sidney's Arcadias - Berrong, Richard M. (The sixteenth century journal, 1991)
Focusing on material wealth and different attitudes toward it from the very opening scene of the "New" Arcadia, Sidney went on to suggest that the possession of such wealth could be a very unreliable indication of nobility, as well as a very real cause of social turmoil. In this respect Sidney made the Arcadia" less a passive mirror of his fellow aristocrats' values and more a critique of them, going so far as to suggest a de-emphasis of financial concern at a time when the English aristocracy was actually becoming ever more pre-occupied with the accumulation and display of wealth.